Isolation, physicochemical and structural characterisation of a novel natural zinc polysaccharide from Crassostrea hongkongensis. (4th November 2022) - Chen, Zhongqin; Han, Rong; Zhou, Longjian; Lin, Haisheng; Cao, Wenhong; Gao, Jialong; Zheng, Huina; Zhang, Chaohua; Qin, Xiaoming
Summary: A novel natural zinc‐enriched polysaccharide: OZPs‐1 was isolated from oyster ( Crassostrea hongkongensis ), with 922.18 μg g −1 of zinc. The physicochemical properties and structural features of OZPs‐1 were systematically studied. The results showed OZPs‐1 was predominantly composed of glucose, with a molecular weight ranging from 4 to 2044 kDa. OZPs‐1 showed favourable thermal stability. NMR analysis showed that there was no sulphate substitution and C‐6 substitution in OZPs‐1, while C‐4 might be the binding site of zinc and polysaccharide. UV, FTIR and XRD spectra suggested ‐OH and ‐COOH group might be involved in the binding of zinc to polysaccharides in OZPs‐1 and there were no ZnO and sulphate substitutions in OZPs‐1. These conclusions indicated that zinc might bind with ‐OH and ‐COOH in C‐4 of polysaccharides and impart the stable structure and favourable physicochemical properties of OZPs‐1, which could facilitate the application of OZPs‐1 as natural organic zinc supplements. Abstract : A novel natural zinc‐enriched polysaccharide (OZPs‐1) from oyster (Crassostrea hongkongensis) was successfully isolated, and the structure analysis showed that zinc might bind with ‐OH and ‐COOH groups in C‐4 of polysaccharides and impart the stable structure and favorable physicochemical properties of OZPs‐1.